Diaphragm rescue alone prevents heart dysfunction in dystrophic mice. - Crisp, A; Yin, H; Goyenvalle, A; Betts, C; Moulton, H; Seow, Y; Babbs, A; Merritt, T; Saleh, A; Gait, M; Stuckey, D; Clarke, K; et al. (2011)
Duchenne muscular dystrophy (DMD) is an X-linked recessive disease caused, in most cases, by the complete absence of the 427 kDa cytoskeletal protein, dystrophin. There is no effective treatment, and affected individuals die from respiratory failure and cardiomyopathy by age 30. Here, we investigated whether cardiomyopathy could be prevented in animal models of DMD by increasing diaphragm utrophin or dystrophin expression and thereby restoring diaphragm function. In a transgenic mdx mouse, where utrophin was over expressed in the skeletal muscle and the diaphragm, but not in the heart, we found cardiac function, specifically right and left ventricular ejection fraction as measured using in vivo magnetic resonance imaging, was restored to wild-type levels. In mdx mice treated with a peptide-conjugated phosphorodiamidate morpholino oligomer (PPMO) that resulted in high levels of dystrophin restoration in the skeletal muscle and the diaphragm only, cardiac function was also restored to wild-type levels. In dystrophin/utrophin-deficient double-knockout (dKO) mice, a more severely affected animal model of DMD, treatment with a PPMO again produced high levels of dystrophin only in the skeletal muscle and the diaphragm, and once more restored cardiac function to wild-type levels. In the dKO mouse, there was no difference in heart function between treatment of the diaphragm plus the heart and treatment of the diaphragm alone. Restoration of diaphragm and other respiratory muscle function, irrespective of the method used, was sufficient to prevent cardiomyopathy in dystrophic mice. This novel mechanism of treating respiratory muscles to prevent cardiomyopathy in dystrophic mice warrants further investigation for its implications on the need to directly treat the heart in DMD.